Impaired Neuropathic Pain and Preserved Acute Pain in Rats Overexpressing Voltage-Gated Potassium Channel Subunit Kv1.2 in Primary Afferent Neurons. (29th January 2014) - Fan, Longchang; Guan, Xiaowei; Wang, Wei; Zhao, Jian-Yuan; Zhang, Hongkang; Tiwari, Vinod; Hoffman, Paul N; Li, Min; Tao, Yuan-Xiang
Voltage-gated potassium (Kv) channels are critical in controlling neuronal excitability and are involved in the induction of neuropathic pain. Therefore, Kv channels might be potential targets for prevention and/or treatment of this disorder. We reported here that a majority of dorsal root ganglion (DRG) neurons were positive for Kv channel alpha subunit Kv1.2. Most of them were large and medium, although there was a variety of sizes. Peripheral nerve injury caused by lumbar (L)5 spinal nerve ligation (SNL) produced a time-dependent reduction in the number of Kv1.2-positive neurons in the ipsilateral L5 DRG, but not in the contralateral L5 DRG. Such reduction was also observed in the ipsilateral L5 DRG on day 7 after sciatic nerve axotomy. Rescuing nerve injury-induced reduction of Kv1.2 in the injured L5 DRG attenuated the development and maintenance of SNL-induced pain hypersensitivity without affecting acute pain and locomotor function. This effect might be attributed to the prevention of SNL-induced upregulation of endogenous Kv1.2 antisense RNA, in addition to the increase in Kv1.2 protein expression, in the injured DRG. Our findings suggest that Kv1.2 may be a novel potential target for preventing and/or treating neuropathic pain.